MANAJEMEN KELAS INKLUSI DI SEKOLAH DASAR DALAM MENDUKUNG PEMBELAJARAN PESERTA DIDIK BERKEBUTUHAN KHUSUS - Dewi Niswatul Fithriyah; Ilma Ariestiana; Alfi Fakhriyyatun Nisrina; Miftakhul Rosyida; Ilma Alfiyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the implementation of inclusive classroom management in elementary schools to support the learning of students with special needs. The study used a qualitative descriptive approach through a literature review related to inclusive education and classroom management practices. The results of the study indicate that effective inclusive classroom management requires a systematic process of planning, organizing, implementing, and controlling that is oriented towards the needs of students. Teachers apply various learning strategies, such as learning differentiation, collaboration between educators, project-based learning, and cooperative learning to increase student participation. In addition, the role of teachers as facilitators, motivators, and mediators, as well as the support of an inclusive school environment, contributes to creating a conducive learning atmosphere. Thus, inclusive classroom management needs to be implemented comprehensively and collaboratively in elementary schools.